A negative-hydrated constriction zone is revealed in the active state of the H v 1 channel - Juan J. Alvear-Arias; Dario Basaez; Emerson M. Carmona; Luciano Galizia; Miguel Fernandez; Antonio Peña-Pichicoi; Marcelo Ozu; Orlando Jorquera; Ramón Latorre; Alan Neely; Jose Antonio Garate; Carlos Gonzalez (Proceedings of the National Academy of Sciences, 2026)
The voltage-gated proton (H v 1) channel is crucial in regulating cellular pH, yet the mechanism underlying proton permeation remains controversial. A deeper understanding of the differences between the channel’s active and resting states is essential for clarifying its conductive properties. In this study, we employ a combination of molecular dynamics simulations, site-directed mutagenesis, and electrophysiological recordings to investigate what changes occur in an active H v 1 channel and how these changes influence conduction properties in the wild-type (WT) channel, a low-conducting N264R mutant, and a superconductive N264E mutant. Our findings reveal that in the active state, interactions are weakened between the selectivity filter, aspartate D160, and the third arginine in the S4 transmembrane segment. This results in a more negatively charged and hydrated environment, which enables proton transport in the WT and N264E channels. Notably, these conformational changes are absent in the N264R mutant. Additionally, our simulations predict—and osmotic shock experiments in oocytes confirm—that an active H v 1 channel can facilitate water permeation. These observations suggest that water conduction occurs as a byproduct of a more dilated and hydrated pathway. We introduce a methodological approach to studying H v 1 by utilizing water permeation as a functional readout. Collectively, our results provide insights into the structural rearrangements of the H v 1 constriction zone, shedding light on how its resting and active configurations govern proton conduction.